Finance and Development, September 1990. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1990)
Providing economic opportunities for the poor and building up their capacity to take advantage of those opportunities can help reduce poverty and ensure sustainable growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet